Development and initial validation of the eating disorder-related rumination assessment scale in a Turkish non-clinical sample - Dilan Gulacan; Caner Doğrusever; Sevgi Bektas-Dag; Guzin Mukaddes Sevincer (BMC Psychology, 2026)
Abstract Objectives There is no valid measurement tool available in Türkiye to assess rumination specific to eating disorders. This study is based on the assumption that conceptualizing rumination within the framework of Goal Progress Theory will enable a comprehensive assessment of goal-related and control-focused cognitive processes, which are characteristic features of eating disorders. Accordingly, the research was conducted to develop and examine the psychometric properties of the Eating Disorder-Related Rumination Assessment Scale (ED-RRA) in a Turkish adult sample. Methods A total of 779 Turkish adult participants (186 men, 593 women) completed the final 12-item ED-RRA. Psychometric analyses included exploratory and confirmatory factor analysis (EFA, n = 392; CFA, n = 387), both estimated with a robust categorical estimator (WLSMV), as well as internal consistency, test-retest reliability, and convergent validity. External validation measures assessing depression (PHQ-9), anxiety (GAD-7), general rumination (RRS), and eating disorder symptoms (EDE-Q) were administered only in the CFA sample ( n = 387). Results Factor analyses supported a single factor. Internal consistency was excellent in both samples (Cronbach’s α = 0.93–0.94; McDonald’s ω = 0.93–0.94), and temporal stability over a 15-day interval was good (ICC = 0.88). The ED-RRA demonstrated strong convergent validity with measures for ED pathology ( r = 0.76). The ED-RRA showed small-to-moderate correlations with the PHQ-9, GAD-7, and RRS ( r = 0.34–0.37). In a hierarchical regression, the ED-RRA predicted ED pathology beyond general rumination, depression, and anxiety (ΔR² = 0.44), although this increment partly reflects content shared with the EDE-Q. Discussion The ED-RRA showed promising preliminary psychometric properties in a non-clinical Turkish adult sample. In contrast to existing measures, it was constructed to target goal-related and control-focused ruminative content. As the present evidence is preliminary and confined to a community sample, the scale is not yet intended for clinical or diagnostic use.